2021
DOI: 10.3390/molecules26082348
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Lowers Blood Glucose and Reduces Oxidative Stress in a Rat Model of Diabetes

Abstract: The aim of the present study was to assess the short-term effects of Thymoquinone (TQ) on oxidative stress, glycaemic control, and renal functions in diabetic rats. DM was induced in groups II and III with a single dose of streptozotocin (STZ), while group I received no medication (control). The rats in groups I and II were then given distilled water, while the rats in group III were given TQ at a dose of 50 mg/kg body weight/day for 4 weeks. Lipid peroxidase, nitric oxide (NO), total antioxidant capacity (TAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“… 46 Another experimental animal study using streptozotocin-induced diabetic rats determined a significant reduction of HbA1c, lipid peroxidase and nitric oxide, and higher total antioxidant capacity (TAC) by the supplementation of 50 mg/kg of thymoquinone daily for 4 weeks. 47 Moreover, an in-vitro study confirmed that thymoquinone has agonistic activity on peroxisome proliferator activated receptor-γ (PPAR-γ). 48…”
Section: Experimental Animal Studies Of N Sativamentioning
confidence: 97%
“… 46 Another experimental animal study using streptozotocin-induced diabetic rats determined a significant reduction of HbA1c, lipid peroxidase and nitric oxide, and higher total antioxidant capacity (TAC) by the supplementation of 50 mg/kg of thymoquinone daily for 4 weeks. 47 Moreover, an in-vitro study confirmed that thymoquinone has agonistic activity on peroxisome proliferator activated receptor-γ (PPAR-γ). 48…”
Section: Experimental Animal Studies Of N Sativamentioning
confidence: 97%
“…TQ as a relatively safe compound and the combination with Vit D has anti-fibrogenic properties and hepato-protective effects against previously established liver fibrosis [ 30 ]. TQ administration can shows lower the levels of oxidative stress and elevation of the total antioxidant capacity indices in diabetic rats [ 31 ]. Furthermore, TQ treatment may improve AChE activity in by chlorpyrifos toxicity and alleviate neuronal injuries and oxidative stress [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin preferentially enters the proximal tubule of the kidney due to the organic cation transporter, triggers apoptosis through the generation of ROS, and induces inflammation, calcium overload, and phospholipase activation, which results in mitochondrial dysfunction and DNA damage (Marullo et al., 2013 ; Soni et al., 2018 ). TQM can operate against nephropathy, has positive antioxidant and anti-apoptotic properties, and is expected to have a nephroprotective effect (Farooqui et al., 2017 ; Dera et al., 2020 ; Faisal Lutfi et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%